Sinergi Pemuda Sibakur dan KKN UNP 2025: Turnamen Wali Nagari CUP 1 (Lomba Voli dan Sepak Bola) Tingkat Kecamatan Tanjung Gadang untuk Membangun Kebersamaan dan Semangat Olahraga - Ali Basrah Pulungan; Aisya Putri Qaimah; Latifa Ananda Putri; Sandra Azzuhra; Shalma Rahayu; Zelvina Wati (CV. ITTC INDONESIA, 2025)
The Wali Nagari Cup 1 tournament, organized by UNP 2025 KKN students in collaboration with the youth of Nagari Sibakur, is a concrete example of collaboration between youth and universities in building togetherness and a spirit of sports at the village level. This activity included two main sports soccer and volleyball participated by various teams from hamlets in Tanjung Gadang District. This study aims to describe how this activity was implemented, the collaboration between various parties, and its impact on social cohesion in the community. The results show that sports at the village level are not only a means of entertainment, but also an effective tool for strengthening social relations, increasing community participation, and affirming local cultural identity. The existence of traditions such as the Singgang Ayam auction also plays a role in strengthening the sense of unity within the community. This study supports previous findings that collaboration between youth, communities, and students can bring about social change that is rooted in local values and is participatory.